Reassessing the Asymmetries and Rigidities in the Interest Rate Pass-Through Process: A Hidden Co-Integration Approach - Yannis Panagopoulos; Aristotelis Spiliotis (Credit and Capital Markets – Kredit und Kapital, 2015)
This paper reassesses the existing asymmetries and rigidities in the interest rate pass-through transmission channels, applied in the advanced economies of the US, the UK, Canada, Japan and the Eurozone. A Crouching Error Correction Model econometric methodology is implemented. The accurate measurement of the different aspects of the pass-through interest rate process has upgraded our understanding related to the behavior of the retail interest rate markets and, perhaps more importantly, enhances our practical efficiency in conducting monetary policy actions, at both a country-by-country and a coordinating level. Our empirical results suggest that monetary policy targeting should rather focus more directly on the money market rates transmission channel, instead of the central bank rates channel. Also, a non-homogenous price-rigid and asymmetric behaviour was found regarding the loan-deposit markets. – – Neubewertung der Asymmetrien und Rigiditäten in dem Zinssatz Übertragungsprozess: Ein Ansatz versteckter Kointegration Diese Arbeit untersucht die bestehenden Asymmetrien und Rigiditäten der Zinstransmissionskanäle in den Industrieländern USA, GB, Kanada, Japan und der Eurozone. Wir verwenden ein "Crouching Error Correction Model" als ökonometrische Methodologie. Die akkurate Messung verschiedener Aspekte des Zinstransmissionsmechanismus verbessert unser Verständnis vom Verhalten der Zinssätze im Kundengeschäft. Des Weiteren kann hierdurch die Effizienz geldpolitischer Maßnahmen auf nationaler und supranationaler Ebene gesteigert werden. Die Ergebnisse unserer empirischen Analyse deuten an, dass sich die Geldpolitik verstärkt an den Transmissionskanälen der Marktzinsen anstelle der Zentralbankzinsen ausrichten sollte. Weiterhin konnte ein inhomogenes, preisstarres und asymmetrisches Verhalten in den Kredit / Einlage-Märkten beobachtet werden.
Keywords: E52; C22; 330; Interest rates pass-through; hidden co-integration; crouching error correction model